Road safety compliance among motorcyclists in Kawempe Division, Kampala, Uganda: a crosssectional study - Ndagire, Margaret; Kiwanuka, Suzanne; Paichadze, Nino; Kobusingye, Olive (International Journal of Injury Control and Safety Promotion, 2019)
Motorcyclists are vulnerable road users in Uganda and 21.7% (3912/18,016) experienced crashes in 2012. This study determined the prevalence of and factors associated with compliance to selected road safety measures (helmet use, retro-reflective jackets use, riding permit and carrying one passenger) among commercial motorcyclists in Kawempe, from April to June 2014 using interviewer administered questionnaires. Total compliance was 0.9% and 24.4% to at least 3/4 measures. Compliance by measure was; 7.6% retroreflective jackets, 28.8% riding permits, 69.4% helmet use and 86.1% carrying one passenger. The associated factors were; knowing that (training before one starts to ride prevents crashes, Adjusted-odds-ratio (AOR) ¼ 2.38 (1.36–4.19), maintaining the motorcycle in good condition prevents crashes, AOR ¼ 0.34 (0.15–0.77) and padding reduces impact of road traffic injury, AOR ¼ 0.37 (0.15–0.89)). Prevalence to compliance is very low. Road safety messages should highlight the importance of all road safety measures to improve compliance.
Keywords: Road safety; Compliance; Motorcyclists; Uganda; Helmet; Retro-reflectors